KAJIAN POTENSI WIRAUSAHA PEREMPUAN DI WILAYAH PESISIR KECAMATAN SANGA-SANGA KABUPATEN KUTAI KARTANEGARA - Gusti Haqiqiansyah; Dayang Diah Fidhiani; Eko Sugiharto (2339-1324, 2014)
The aim of study was to search the potency of women’s entrepreneurship in the coastal communities of Sanga-Sanga Sub-district, Kutai Kartanegara District. The study was conducted by using survey method, i.e. direct observation and interviews with coastal community informants, especially women. Data were analyzed by descriptive and financial analysis. The results showed that fishery businesses in the research area are concentrated on fishing, fish culture and processing of fishery products activities. Fish processing activities done by women in the studied area involve ‘amplang’, crackers, and fish meatballs business. The potency of coastal women's entrepreneurship include the usage of free time to work for family income addition, personal development to create more productive business, and the division of time between taking care of the household members and conducting productive activities.